â‘
\begin{align}
V & := \{ \textbf{x,y,z},a,b \in \Bbb{F} :\\
\textbf{x}+\textbf{0} & = \textbf{x}\\
\textbf{x}1 & = \textbf{x}\\
a(b\textbf{x}) & = (ab)\textbf{x}\\
(\textbf{x}+ \textbf{y}) + \textbf{z} & = \textbf{x} + (\textbf{y} + \textbf{z})\\
\textbf{x}+ \textbf{y} & = \textbf{y} + \textbf{x}\\
\textbf{x}+ (-\textbf{x}) & = \textbf{0}\\
a(\textbf{x}+ \textbf{y}) & = a\textbf{x}+ a\textbf{y}\\
(a + b)\textbf{x} & = a\textbf{x}+ b\textbf{x}\}\\
\end{align}
â‘¡
\begin{align}
\textbf{x} : V \mapsto \Bbb{F}\\